Hubungan Manajemen Waktu Belajar dan Hasil Belajar Peserta Didik Kelas V SDN 104256 Rugemuk - Siti Fatimah; Doddy Feliks P. Ambarita; Irsan Irsan; Wildansyah Lubis; Septian Prawijaya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study was conducted with the aim of determining the relationship between time management and the learning outcomes of grade V students of SDN 104256 Rugemuk in the Social Studies subject "Chapter 3: Magnets, Electricity and Technology for Life". This type of research is quantitative with the research method used is correlation. The subjects of this study were 30 people. Data collection techniques in this study consisted of questionnaires and documentation. The data analysis technique used was Product Moment correlation. The results of the study showed a relationship between learning time management and student learning outcomes because the results of the analysis showed that rcount > rtable, namely 0.627 > 0.361, which means that there is a relationship between time management and learning outcomes.